Ask a New Question
Search
Solve by the equatic formula
Showing results
1
through
10
of 86,521.
Solve by the equatic formula. 6x^2-2x-1=0
2 answers
asked by
Kimberly Williams
375 views
Solve by the equatic formula. 4x^2+x-1=0
1 answer
asked by
Kimberly Williams
336 views
Solve by the equatic formula and simplify. x^2-3x-1=0
1 answer
asked by
Kimberly Williams
324 views
solve for x
(24+2x)(10+2x) - 240 = 152 First multiply. 24(10) = ___ 2x (2x) = ____ Now subtract 240. Can you finish the problem
0 answers
asked by
q
656 views
Please help to solve to find x,y
1. y=7x-3 2. 4x+2y=8 Take the value of y in the first formula and substitute it for y in the
1 answer
asked by
Lee
720 views
how would i work out the following problems
solve each formula in terms of the given variable 1. 5d-2g=9 ;g The formula A=2h(l+w)
1 answer
asked by
jessica
789 views
For these problem, I know how to solve it, but I have some issues with the formula. I know that, I need to write down the
2 answers
asked by
hh
869 views
use substitution to solve the linear system
3x+2y=-5 4x-3y=16 help plz!!! Solve for y in one formula, and then substitute that
1 answer
asked by
kerry
1,439 views
use substitution to solve the linear system
3x-y=15 x+2y=-2 Solve for y in one formula, and then substitute that value for y in
0 answers
asked by
lisa
631 views
Recall the compound interest formula A = a(1 + r/k)^(kt). Use the definition of a logarithm along with properties of logarithms
1 answer
asked by
Anonymous
365 views
Pages
1
2
3
4
5
6
7
8
9
10